Sequential and global optimization in powder injection molding processing - Ayad, Ghassane; Barriere, Thierry; Gelin, Jean-Claude; Song, Jiupeng; Liu, Baosheng (European Journal of Computational Mechanics, 2008)
The work is focused on the overall optimization associated to powder injection molding (PIM). The PIM process includes four main stages, from the mixture of the powders and binders to the final sintering stage. Injection and sintering stages are considered to be the most important for optimization, as they mostly affect the final quality of the produced components. The injection stage shapes the green parts but initiates powders segregation that will be inherited and amplified by the sintering stage to finally appear in the resulting products. One first introduces an optimization loop based on the surfaces response method to minimize the powder segregation. Then the results are transferred to a sintering optimization loop applied through an experimentally calibrated thermo-mechanical creep model to predict the shrinkage and density contours on the final parts. The overall optimization combines both optimizers based on the developed simulation tools to provide a realistic way to improve the PIM process design accounting the different processing stages.